2009
DOI: 10.4049/jimmunol.0804018
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Presentation of Male Seminal Fluid Antigens Elicits T Cell Activation to Initiate the Female Immune Response to Pregnancy

Abstract: The events that generate T cell-mediated immune tolerance in early pregnancy are ill-defined. To investigate the significance of seminal fluid Ags in activating maternal T cells, and define the underlying Ag presentation pathways, OVA-specific T cells were adoptively transferred to female mice inseminated by males ubiquitously expressing membrane-bound OVA. OVA-reactive CD8+ OT-I and CD4+ OT-II T cells transferred to mated recipients expressed activation markers CD25 and CD69 and proliferated vigorously in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
214
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(234 citation statements)
references
References 78 publications
15
214
0
5
Order By: Relevance
“…Exposure to seminal plasma not only induces an inflammatory response in the female genital mucosa, but also induces regulatory mechanisms that allow the fetus (a semiallograft) to grow and develop in the uterus. In this regard, it has been clearly demonstrated in mouse models that exposure of the female genital mucosa to seminal plasma induces the expansion of CD4 + CD25 + FOXP3 + Tregs in the lymph nodes draining the uterus, promoting tolerance to paternal alloantigens (17,18). This occurs even in the absence of conception, thus suggesting a critical role for seminal fluid as an inducer of Treg (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to seminal plasma not only induces an inflammatory response in the female genital mucosa, but also induces regulatory mechanisms that allow the fetus (a semiallograft) to grow and develop in the uterus. In this regard, it has been clearly demonstrated in mouse models that exposure of the female genital mucosa to seminal plasma induces the expansion of CD4 + CD25 + FOXP3 + Tregs in the lymph nodes draining the uterus, promoting tolerance to paternal alloantigens (17,18). This occurs even in the absence of conception, thus suggesting a critical role for seminal fluid as an inducer of Treg (45).…”
Section: Discussionmentioning
confidence: 99%
“…This inflammatory response appears to be mediated, at least in part, by the three isoforms of TGF-b (TGF-b1, TGF-b2, and TGF-b3) that are found at high concentration in human semen (16). In contrast, in mouse models, the same group has shown that seminal plasma induces the expansion of regulatory T cells (Tregs) specific to seminal Ags in the receptive partner, leading to the expansion of Tregs, which subsequently migrate to the endometrium and promote tolerance to paternal alloantigens avoiding allogeneic fetal rejection (17,18).…”
mentioning
confidence: 99%
“…Three days later, transferred Tg T cells were recovered from the footpad-draining (popliteal) LN and assessed for CFSE dye dilution as a direct measure of OVA-specific Tg CD8 ϩ T-cell proliferation resulting from MHC-I-restricted OVA antigen expression (31, 45). The degree of OT-I proliferation has previously been shown to correlate with the level of OVA antigen expression and, hence, provides an opportunity to track the location and extent of antigen expression in vivo (29,34). As shown in representative proliferation plots from individual mice (Fig.…”
Section: Type I Ifn Receptor Expression Does Not Affect Fpv-mediated mentioning
confidence: 99%
“…The physiology of murine placentation is markedly different to that of the humans, but murine models have been used to study the development of fetus-specific cellular immune responses during pregnancy. Fetal Ags have been shown to accumulate in peripheral and central lymph nodes that drain the uterus (14), and paternal Ags can be cross-presented by maternal APCs (15). Several murine models have demonstrated the presence of fetal-specific CD8 + T cells during pregnancy (16).…”
mentioning
confidence: 99%